2019
DOI: 10.1097/sap.0000000000001685
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Frameshift Mutation of GLI3 Causes Isolated Postaxial Polydactyly

Abstract: Background GLI3 encodes a transcription factor in the sonic hedgehog signaling pathway, which is essential in regulating the human limb bud development, especially on the anteroposterior axis. Mutations in GLI3 have been confirmed to be associated with various human congenital malformations, including Greig cephalopolysyndactyly syndrome, Pallister-Hall syndrome, and isolated polydactyly. A robust gene-phenotype relationship between GLI3 and Greig cephalopolysyndac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It has been demonstrated that GLI3 possesses a dual function, including a transcriptional activator of SHH signaling pathway by phosphorylated full‐length GLI3 and a repressor by C‐terminally truncated CLI3. Recently, several novel mutations of GLI3 have been identified in the patients with PD, including mutation c. 1622C > T (Zou et al, 2019), c.2148delA (Zhao, Xu, Liu, & Li, 2019), c.3437_3453delTCGAGCAGCCCTGCCCC, and c.3997C > T (Chen et al, 2019), c.1180C > TT (Ni et al, 2019). Therefore, our results suggested that this frameshift mutation of GLI3 might be a main reason for preaxial PD type IV phenotype in this Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GLI3 possesses a dual function, including a transcriptional activator of SHH signaling pathway by phosphorylated full‐length GLI3 and a repressor by C‐terminally truncated CLI3. Recently, several novel mutations of GLI3 have been identified in the patients with PD, including mutation c. 1622C > T (Zou et al, 2019), c.2148delA (Zhao, Xu, Liu, & Li, 2019), c.3437_3453delTCGAGCAGCCCTGCCCC, and c.3997C > T (Chen et al, 2019), c.1180C > TT (Ni et al, 2019). Therefore, our results suggested that this frameshift mutation of GLI3 might be a main reason for preaxial PD type IV phenotype in this Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have elucidated genotype–phenotype correlation in terms of location of the mutation in particular domain and the resulting phenotype (Ni et al, ; Wang et al, ). Currently, most GLI3 mutations causing syndromic and nonsyndromic phenotypes are loss‐of‐function variants (Ni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have elucidated genotype–phenotype correlation in terms of location of the mutation in particular domain and the resulting phenotype (Ni et al, ; Wang et al, ). Currently, most GLI3 mutations causing syndromic and nonsyndromic phenotypes are loss‐of‐function variants (Ni et al, ). Mutations in N‐terminal and the C‐terminal regions are mostly associated with the GCPS, while the PHS phenotype mostly results due to mutations in the central part of the protein (Demurger et al, ; Jamsheer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a greater spectrum of pathogenic variants located before 1998 nt and after 3481 nt of GLI3 cDNA cause loss of function and manifest in GCPS (Furniss, Critchley, Giele, & Wilkie, ; Johnston et al, ; Kalff‐Suske et al, ). The underlying mechanism of the influence of the location of the variants on different syndromes is still unknown (Ni et al, ). The haploinsufficiency of GLI3 is however proposed to be the main mechanism of the pathogenesis of GCPS.…”
Section: Discussionmentioning
confidence: 99%